Micromollusk families in 2 contrasting seasons in Bahia de los Angeles, Gulf of California, Mexico - Elena Solana-Arellano; Victoria Díaz-Castañeda; Olga Flores-Uzeta (Ciencias Marinas, 2023)
Marine mollusks provide important ecosystem services. They create habitats for benthic organisms, filter water, biodeposit organic carbon in the seafloor, and serve as food sources for other organisms. Studies of mollusk diversity require time-consuming methods to process samples and identify species. Thus, it is not surprising that most studies have focused on macromollusks that can be collected and processed easily, ignoring micromollusk species. Without understanding the ecology and distributions of micromollusks properly, it is impossible to assess their populations and implement adequate conservation measures. Here we present microgastropods collected in Bahia de los Angeles at the family level for September 2013 (summer) and February 2014 (winter). During each season, we sampled 6 coastal sediment stations, and analyzed depth, salinity, temperature, granulometry, and organic matter. A total of 20,353 specimens were collected: 15,310 in summer and 5,043 in winter. Seven micromollusk families were identified: Barleeidae, Caecidae, Cerithiidae, Eulimidae, Pyramidellidae, Rissoidae, and Tornidae. Caecidae and Barleeidae exhibited the highest densities among all families in summer and winter, respectively (278,044 ind·m–2, 142,222 ind·m–2). The lowest densities for summer and winter were observed for the Tornidae family (~1,867 ind·m–2, ~1,411 ind·m–2). Barleeidae, Caecidae, Cerithiidae, Rissoidae, and Tornidae were classified as herbivorous and detritivorous; Eulimidae and Pyramidellidae, as carnivorous and ectoparasitic. Tornidae and Eulimidae showed symbiotic relationships with various invertebrate species. The Bayesian analysis of variance indicated a high probability of differences only in summer (BF > 3). When comparing the stations in both periods, all stations, except station 6, showed differences between periods (BF > 3). The canonical correlation analysis indicated some associations between family abundances and temperature. This study provides valuable information that expands the knowledge of micromollusk biodiversity in the coastal area of Bahia de los Angeles, an important site for conservation in Mexico.